Latihan Kerja dan Kegiatan Produksi Narapidana Sebagai Model Pembinaan Kemandirian dan Pencapaian Lembaga Pemasyarakatan Industri - Muh Khamdan Khamdan; Wiharyani; Rini Setiawati (Madani : Indonesian Journal of Civil Society, 2024)
Following a rigorous, carefully concerns and considered review of the article published in Madani : Indonesian Journal of Civil Society to article entitled “Latihan Kerja dan Kegiatan Produksi Narapidana Sebagai Model Pembinaan Kemandirian dan Pencapaian Lembaga Pemasyarakatan Industri” Vol 6, No 2, pp. 43-53, August 2024, DOI: https://doi.org/10.35970/madani.v6i2.2219. This paper has been found to be in violation of the Madani : Indonesian Journal of Civil Society Publication principles and has been retracted. The article contained redundant material, the editor investigated and found that the paper published in JMM (Jurnal Masyarakat Mandiri), Vol. 8, No. 2 (August 2024), pp. 1957-1967, DOI: https://doi.org/10.31764/jmm.v8i2.21782, entitled "Latihan Kerja dan Kegiatan Produksi Narapidana Sebagai Model Pembinaan Kemandirian dan Pencapaian Lembaga Pemasyarakatan Industri ". The document and its content has been removed from Madani : Indonesian Journal of Civil Society, and reasonable effort should be made to remove all references to this article.